LEADERSHIP, ETHICS AND ACCOUNTABILITY IN GOVERNANCE - Kulkarni, Tejaswini Ganapatrao (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Prajasukhe Sukh Rajna: Prajanan tu hite hitam. Natmapriya hitam Rajna: Prajanan tu priyaam hitam ॥ (1) The happiness of the king lies in the happiness of the people, he should show his interest in the interests of the people. The interest of the king is not in what is dear to himself, his interest is in what is dear to the people. Kautilya's Arthasastra is an excellent book on the subject of leadership ethics and responsibility in governance. The soul of the state resides in leadership. This is true. Therefore, effective and practical leadership is an essential requirement in statecraft. Acharya (Chanakya) Kautilya's great The text 'Artha Shastra' is a book which deals mainly with economic administration. Kautilya's Arthashastra, an ancient Indian political treatise, provides a comprehensive guide to governance, economics and the art of governance. Its major theories revolve around leadership, law and economy.